Radiography of OS Calcaneus with Spur Study Formation at Columbia Asia Hospital Medan - Sidauruk, Juliana; Simamora, Djamiandar (PT Inovasi Pratama Internasional, 2023)
Radiographic examination of the calcaneus bone using X-rays can clearly determine the location of the spur formation. The aim of this study was to determine the procedure for carrying out Os Calcaneus radiography with suspected spur formation at Columbia Asia Hospital, Medan. The type of examination used is descriptive qualitative. Data collection techniques are based on the results of literature reviews, interviews, observations and documentation. This examination was carried out at Columbia Asia Hospital Medan, in January 2020, using a General X-ray unit x-ray, 18 cm x 24 cm cassette, with image processing using Computed Radiography. The results of the research obtained radiographic images of the calcaneus bone with greater detail and sharpness, so that it could show spur formation on the calcaneus bone. To show the anatomical picture and pathological abnormalities in the Os Calcaneus with suspected spur formation, it can be done using Axial and Lateral projections.